New records of oribatid mites (Acari: Oribatida) from Argentina - Ruiz, Erica Vanesa (2018)
A taxonomic inventory of oribatid mites from lenga forests in Patagonia Argentina was carried out to assess the taxonomic diversity and to increase the knowledge of their distribution. Nine new records of soil oribatid mites from Argentina are reported. Those species were collected in Chubut province and Tierra del Fuego province. The new registered species belong to the genera Lamellozetes, Hermannia (Phyllhermannia), Crotonia, Kokoppia, Acutoppia, Lanceoppia (Baioppia), Loboppia, Membranoppia(Membranoppia) and Graptoppia (Stenoppia).